Sinergisitas Stakeholder dalam Pengembangan Mutu Pendidikan PAI di SMP N 01 Pajar Bulan - Fitri Adeanti Riski (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
ABSTRACT The aim of this research is to increase knowledge about the role of stakeholders in developing the quality of PAI learning. Schools are a service product in education; the services referred to serve the needs of parents for their children's education, especially the needs for junior high school children's education. The choice of parents in choosing a school for their children is different from choosing a secondary school; many factors will One of the considerations for parents to make their choice is references from people they are close to or well known to who send their children to that school. This reference factor must be managed well by internal school parties with external stakeholders as quality guarantors in convincing parents of prospective students of the quality of the school institution. The goals of education in schools will be achieved if all internal components of the school can work together well and not just the internal components of the school; of course, components from outside the school are needed; the external elements of the school consist of parents of students or the surrounding community who have an interest either directly or indirectly within school institutions, the role of these external stakeholders is vital in ensuring the quality of junior high schools so that they run well and stably. Keywords: junior high school children's education, education stakeholders